A Wideband Multilayer Quasi‐Yagi Antenna with a Simplified Microstrip‐to‐CPS Transition Based on LTCC Technology. Issue 8 (28th May 2013) - Wang, Jinhong; Sang, Lei; Wang, Zhigang; Xu, Ruimin; Yan, Bo
ABSTRACT In this article, a wideband multilayer quasi‐Yagi antenna using low temperature cofired ceramic technology is presented. The antenna is fed by a simplified microstrip‐to‐coplanar strip transition, which serves as balun and impedance transformer simultaneously. Multilayer directors are flared to direct the antenna propagation toward the end‐fire direction. Compared with the traditional planar quasi‐Yagi antenna, they can suppress the surface waves significantly and provide better director effect to improve the radiation performance. Furthermore, they excite multiple adjacent resonant modes to broaden the bandwidth. The measured results show that the proposed antenna achieves a wide bandwidth of 60% for S11 < −10 dB (26.8–49.8 GHz), better than 12 dB front‐to‐back ratio, smaller than 16 dB cross polarization and 4.5–6.9 dBi gain within the bandwidth. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1959–1963, 2013